Association of Plasma Atherogenic Index (PAI) with arterial stiffness in normotensive versus hypertensive Patients - Ain, Qurat Ul; Younas, Muhammad; khan, Muhammad Qaisar Alam; Niaz, Ayesha; Haroon, Zujaja Hina; Anwar, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To find Association of Plasma Atherogenic Index with Arterial stiffness in normotensive and hypertensive patients. Study Design: Diagnostic Accuracy Study. Place and Duration of Study: Armed Forces Institute of Cardiology (AFIC) and Department of Chemical Pathology, Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Oct 2022 to May 2023. Methodology: Hypertensive and normotensive patients with age group of 30-50 years were included in this study. Semi-structured Questionnaire was structured to collect the information regarding demographics, any comorbidity and medication history. Results: Total 140 subjects were included in current research at AFIC. Altogether, 92(65.7%) male and 48(34.3%) female were participated. Plasma Atherogenic Index (PAI) is derived Index used for current study and it is divided into low risk (0.1), Intermediate risk (0.1-0.24) and high risk (>0.24). Out of all patients 13(9.3%) were in low risk, 38(27.1%) were in intermediate risk and 89(63.6%) were in high risk category. For association between PWV and PAI with blood pressure computed results showed significant association with p-value <0.001 for both PWV and PAI. Conclusion: There is strong association between PAI and PWV with hypertension. A calculated index of lipid profile can be used as early predictor for arterial stiffness. PAI can be used as an alternative of PWV as an early screening marker for arterial stiffness in all cardiovascular risk factors.